Unheard voices speak up : the Arabidopsis community and the representation of researchers from the Global South - Auge, Gabriela; Estevez, José M. (Oxford University Press, 2024)
In June 2023, the Arabidopsis community met in Makuhari, Chiba, Japan, for the 33rd International Conference in Arabidopsis Research (ICAR). The meeting, at which more than 1200 researchers gathered, spanned the course of 5 days showcasing three keynote lectures, six plenary sessions, 11 workshops, and 33 concurrent sessions, in addition to two poster sessions.